Sexual Violence in an Islamic Higher Education Institution of Indonesian: A Maqasid Al-Shariah and Foucauldian Perspective - Muhsin, Ilyya; Ma’mun, Sukron; Nuroniyah, Wardah (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
Sexual violence was prevalent in many settings, including in religious educational institutions. This article analyzed cases of sexual violence at an Islamic higher education institution in West Java, Indonesia, using the maqasid al-shariah and Foucault's theory of sexuality as the theoretical frameworks. This mixed-method research used Google form's surveys, in-depth interviews, and observations as the data collection methods. The data were analyzed using a flow model, which comprised selection, display, analysis or discussion, and conclusion. This study showed that verbal and non-verbal sexual violence was rampant. It occurred between student and student, lecturer and staff, staff and staff, and lecturer and student. Four models of sexual violence were found based on the typology designed by Dzeich and Weiner, who categorized thirteen forms of sexual violence. The maqasid al-shariah analysis outlined that sexual violence was against the fundamental values and objectives of sharia and human rights. Additionally, Foucault's theory identified patriarchal and cultural hegemony aspects in sexual violence. This study's intriguing part was the findings that combined in-depth interviews, observations, and surveys, intended to understand the intensity of existing cases. On the other hand, the power of analysis was centered on normative fiqh and sociological aspects. According to the literature reviews, these two approaches had not been administered by previous researchers.